Analysis of the agreements of the Council of Ministers for Sustainability - Reicher Salazar, Oscar (Revista de Derecho Ambiental, 2021)
In 2010, Chile’s environmental institutions were reformed by creating a Council of Ministers for Sustainability (CMS). The reason behind this modification was that before the reform, each sector could issue general or specific administrative acts on environmental matters without the participation of the environmental authority. Given this situation, the CMS is given the competence to pronounce on draft laws and administrative acts that derive from both the environmental authority and the sectoral bodies with competence in the matter. However, after 10 years of implementation of this reform, it is necessary to review whether the reform has achieved its stated objective. To this end, the agreements adopted by the CMS were reviewed following the session minutes published on the CMS website for the period 2010-2020. The results show that the creation of the CMS has not contributed significantly to the incorporation of the environmental variable, in addition to a concentration of the type of use of management instruments. Furthermore, it shows that protected area agreements play an important role in the joint management by the Ministry of Environment with other sectoral ministries.